Rising South Korea: A Minor Player or a Regional Power?1. (December 2013) - Shim, David; Flamm, Patrick
<x xml:space="preserve">Abstract</x> South Korea's rising status in regional and global affairs has received significant attention in recent years. In academic, media, and policy debates, though, South Korea is usually regarded as a mere middle power that, due to its geopolitical situation, has only limited leeway in its foreign policy choices. Accordingly, it must constantly maneuver between its larger neighbors: China, Japan, and Russia. However, this perspective negates the fact that the same geopolitical constraints also apply to other states in the region. Thus no country can easily project its power onto others. We use the concept of "regional power" as a template for investigating South Korea's rising stature in regional and global politics, and argue that Seoul appears quite capable of keeping up with other assumed regional powers. Hence, we not only provide a novel account of South Korea's foreign policy options but also go beyond current approaches by asking about the (undetermined) possibilities that exist for Seoul's regional relations.